2014
DOI: 10.1002/fsn3.122
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 induction properties of food and herbal‐derived compounds using a novel multiplex RT‐qPCR in vitro assay, a drug–food interaction prediction tool

Abstract: A multiplex RT-qPCR was developed to examine CYP1A2, CYP2D6, and CYP3A4 induction properties of compounds from food and herbal sources. The induction of drug metabolizing enzymes is an important pharmacokinetic interaction with unique features in comparison with inhibition of metabolizing enzymes. Cytochrome induction can lead to serious drug–drug or drug–food interactions, especially if the coadministered drug plasma level is critical as it can reduce therapeutic effects and cause complications. Using this op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Increase in MRT, Cl and Vd of 6‐MNA in APE + NAB treated group reveals that other components of APE other than AN might be interfering in metabolism of NAB. As per the previous studies, AN induces CYP1A2 (Jaruchotikamol et al ., ; Pekthong et al , ; Koe et al , ) and also inhibits CYP1A2 (Ooi et al ., ; Chen et al , ). APE has CYP1A2 inhibitory activity in vitro (Pekthong et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in MRT, Cl and Vd of 6‐MNA in APE + NAB treated group reveals that other components of APE other than AN might be interfering in metabolism of NAB. As per the previous studies, AN induces CYP1A2 (Jaruchotikamol et al ., ; Pekthong et al , ; Koe et al , ) and also inhibits CYP1A2 (Ooi et al ., ; Chen et al , ). APE has CYP1A2 inhibitory activity in vitro (Pekthong et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In this direction, studies are being conducted to develop methods for evaluating food-drug interactions. For example, Koe and coworkers recently developed a novel multiplex RT-qPCR in vitro assay to examine the P450 enzyme-induction properties of herb-derived compounds [ 147 ].…”
Section: Modulation Of Cyp3a4 Activity By Polyphenolsmentioning
confidence: 99%
“…The possible therapeutic effects of curcumin on several diseases are mainly associated with inhibition of oxidative stress and its downstream mediators. Several studies have evidently shown that curcumin inhibits free radical formation (Jain et al 2015), lipid peroxidation (Al-Rubaei et al 2014), DNA damage (Tokac et al 2013), and damage to cytochrome p450, but it induces glutathione-S-transferase (Koe et al 2014). …”
Section: Curcuminmentioning
confidence: 99%